O processo terapêutico em uma psicoterapia psicanalítica interrompida com paciente com transtorno de personalidade borderline - Campezatto, Paula Von Mengden (2016)
The purpose of this Doctoral Thesis was to describe and understand a interrupted psychoanalytic psychotherapy process in a patient with Borderline Personality Disorder. It is a naturalistic systematic case study held from recordings of psychotherapy sessions and its supervision of the case. Instruments: Instrument to Assess Psychoanalytic Sessions (IASP), Therapeutic Cycles Model (TCM), Psychotherapy Process Q-Set (PQS) and Working Alliance Inventory - observational version (WAI-O). Initially, it presents a contextualization of research followed by four studies: Study 1: This is a systematic review of psychotherapy and results. STUDY 2: Investigated the technique used in the treatment by the IASP. The results indicated that most sessions of the treatment were psychoanalytic, although three sessions have been classified as non-psychoanalysis. The most and the least session adhered to technique were analyzed. STUDY 3: Described the therapeutic process combining TCM and PQS. The case was divided at a time with change cycles and a time without change cycles. The content covered by the duo therapist-patient was relevant to psychotherapy and related to the diagnosis of the patient. However, the patient showed unengaged with the process and went on to not rely on the therapist to solve her problems. STUDY 4: The instruments IASP, TCM, PQS and WAI-O were joined to understand the outcome of the case. It was identified that the patient showed unengaged with the therapeutic process and there were ruptures in the therapeutic alliance. Implications of the findings and limitations of the study were discussed.